2015
DOI: 10.18632/oncotarget.6520
|View full text |Cite
|
Sign up to set email alerts
|

Human β-defensin 3 contains an oncolytic motif that binds PI(4,5)P2 to mediate tumour cell permeabilisation

Abstract: Cationic antimicrobial peptides (CAPs), including taxonomically diverse defensins, are innate defense molecules that display potent antimicrobial and immunomodulatory activities. Specific CAPs have also been shown to possess anticancer activities; however, their mechanisms of action are not well defined. Recently, the plant defensin NaD1 was shown to induce tumour cell lysis by directly binding to the plasma membrane phosphoinositide, phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2). The NaD1–lipid interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 84 publications
8
69
0
Order By: Relevance
“…Some studies indicated that defensin promoted cancer growth (21,22), whereas other studies showed that defensin is cytotoxic (16,17,(23)(24)(25)(26). Our results suggest that the cytotoxic effect is specific to hBD3 and its mouse homolog, Defb14, among members of the defensin family.…”
Section: Figure 3 Time Dependency Of Cellular Damage Induced By Humamentioning
confidence: 60%
See 1 more Smart Citation
“…Some studies indicated that defensin promoted cancer growth (21,22), whereas other studies showed that defensin is cytotoxic (16,17,(23)(24)(25)(26). Our results suggest that the cytotoxic effect is specific to hBD3 and its mouse homolog, Defb14, among members of the defensin family.…”
Section: Figure 3 Time Dependency Of Cellular Damage Induced By Humamentioning
confidence: 60%
“…Winter et al indicated that hBD3 inhibited colon cancer-cell migration, although not cell proliferation (16). Moreover, Phan et al indicated that hBD3 exhibits anticancer effects on various tumor cells through cell permeabilization (17).…”
mentioning
confidence: 99%
“…Moreover, substantial inhibition of HBD‐3‐induced TNF and IL‐6 release was also observed upon treatment of HBD‐3 with synthetic PI(4,5)P 2 and other PIPs, but not PA, or the incubation of monocytes with PI(4,5)P 2 ‐sequestering neomycin (Figure ). In our previous report, HBD‐3 was demonstrated to internalize and directly bind to cellular PI(4,5)P 2 , while the HBD‐3 mutants, synthetic PIPs and neomycin were shown to impede this interaction (and PI(4,5)P 2 ‐mediated cancer cell membrane permeabilization by HBD‐3) . The HBD‐3:PI(4,5)P 2 interaction is not simply based on “non‐specific” electrostatic forces, as it appears to be structurally‐dependent.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, HBD‐3 internalization into leukocytes has been consistently reported, although its relevance in immunomodulation is currently unknown . In our previous report,HBD‐3 was demonstrated to internalize into mammalian cells and bind to phosphatidylinositol 4,5‐bisphosphate [PI(4,5)P 2 ] at the inner leaflet through its cationic β2‐β3 loop (K 32 CSTRGRK 39 ), with K32 and K39 being particularly important for PI(4,5)P 2 interaction. PI(4,5)P 2 and other phosphorylated derivatives of phosphatidylinositol, which are collectively known as phosphoinositides (PIPs), are minor membrane phospholipids but serve important roles in diverse cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…LPA, lysophosphatidic acid; LPC, lysophosphocholine; PI, phosphatidylinositol; pPI(3)P, phosphatidylinositol 3-phosphate; PI(4)P, phosphatidylinositol 4-phosphate; PI(5)P, phosphatidylinositol 5-phosphate; PE, phosphatidylethanolamine; PC, phosphatidylcholine; S1P, sphingosine 1-phosphate; PI(3,4)P 2 , phosphatidylinositol 3,4-bisphosphate; PI(3,5)P 2 , phosphatidylinositol 3,5-bisphosphate; PI(4,5)P 2 , phosphatidylinositol 4,5-bisphosphate; PI(3,4,5)P 3 , phosphatidylinositol 3,4,5-trisphosphate; PA, phosphatidic acid; PS, phosphatidylserine; blue blank, lipid-negative control. (23) and blocks the antitumor activity of NaD1 and other defensins that bind to PI(4,5)P 2 (11,17). To determine whether neomycin could block the antifungal activity of NaD1, we employed the model yeast S. cerevisiae, as the antifungal mechanism of action of NaD1 is conserved between filamentous fungi and yeast (21,24).…”
Section: Figmentioning
confidence: 99%